Evaluation of natural phosphate (Fosbio®) in the “safrinha” corn (Research, Society and Development, 2023)
The objective of this research was to evaluate the efficiency of phosphating with Fosbio® (Rocafeed) in a corn production system in relation to phosphorus and boron contents of 0 - 20 cm and 20 - 40 cm. The research was carried out at Fazenda Santa Cruz in Paraguaçu-MG from February to August 2023. The chemical and granulometric parameters of the soil were analyzed, and based on the data obtained, the amount of Phosbio® to be applied was calculated. on the land, which was applied by broadcast on 02/23/23, and then, the application of natural phosphate was carried out and, subsequently, the sowing of corn (Pioneer P3440 PWU) which took place in february. The treatments were as follows: T1 - Control, T2 - 516 kg ha-1 of Fosbio® and T3 - 1235 kg ha-1 of Fosbio®. The experiment was installed in a Randomized Block Design (RBD) with 5 replications per treatment, with the parameters evaluated being corn productivity, phosphorus (P) and boron (B) content in the soil before planting and after harvesting in layers of 0 -20 cm and 20-40 cm. The means obtained were compared using the Scott-Knott test with 5% probability, using the SISVAR® software. The application of Fosbio® 00-25-00+0.5 boron at a dosage of 516 kg/ha-1, promoted an improvement in phosphorus levels in the soil, both evaluated by the resin extractor and Mehlich, and for the boron element the application increasing dosages promoted an increase in the element content in the soil.